Herling-Grudziński w dyskusji z Norwidem, Krasińskim i Mickiewiczem - Walczak, Albert (Archiwum Emigracji, 2020)
HERLING-GRUDZIŃSKI IN DISCUSSION WITH NORWID, KRASIŃSKI, AND MICKIEWICZ The article consists of three parts, each focusing on a different essay of Herling’s concerning the Romantic era. The author demonstrates how Herling reads Romantic works in order to search for valuable clues for 20th-century Polish immigrants. It appears that it is Cyprian Norwid and his sometimes critical view of the legacy of Romanticism that prove to be particularly appealing for Herling. The article also presents Herling’s views on Zygmunt Krasiński’s Nie-Boska Komedia [Non-Divine Comedy], in particular the Romantic representations of aristocracy and revolutionaries. It closes with an analysis of Księgi narodu polskiego i pielgrzymstwa polskiego [The Books and the Pilgrimage of the Polish Nation] by Adam Mickiewicz. Although Herling is skeptical of many of Mickiewicz’s views, especially messianism, he can also see how his work still remains topical.